Xanthones from Triperospermum chinense (Migo) - ZHU, KAI-CHENG; MA, CHUN-HUI; FAN, MING-SONG; YE, GUAN; HUANG, CHENG-GANG (Asian Journal of Chemistry, 2010)
Five xanthones including 1,3-dihydroxy-5,8-dimethoxyxanthone (1), 1,3,7-trihydroxy-8-methoxy xanthone (2), 8-hydroxy- 1,2,6-trimethoxy xanthone (3), 1,7-dihydroxy-3,8-dimethoxyxanthone (4), 1,2,8-trihydroxy-5,6-dimethoxyxanthone (5) were isolated from 95% ethanolic extract of Triperospermum chinense (Migo) by chromatographic techniques. The structure of these compounds were determined by spectral techniques (UV, IR, MS and NMR). All the compounds were isolated from this genus for the first time.